1999
DOI: 10.1046/j.1432-1327.1999.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation of DNA methyltransferase gene expression by methylation

Abstract: This paper tests the hypothesis that expression of the DNA methyltransferase, dnmt1, gene is regulated by a methylation-sensitive DNA element. Methylation of DNA is an attractive system for feedback regulation of DNA methyltransferase as the final product of the reaction, methylated DNA, can regulate gene expression in cis. We show that an AP-1-dependent regulatory element of dnmt1 is heavily methylated in most somatic tissues and in the mouse embryonal cell line, P19, and completely unmethylated in a mouse ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…An eight-fold increase in Dnmt-1 mRNA induction was observed when cells were challenged by 5-azacytidine, a methylation inhibitor. Moreover, rodents fed methionine-deficient diets exhibited both global hypomethylation and increased Dnmt-1 expression and activity (Slack et al 1999).…”
Section: Heterozygous Reeler Micementioning
confidence: 99%
See 1 more Smart Citation
“…An eight-fold increase in Dnmt-1 mRNA induction was observed when cells were challenged by 5-azacytidine, a methylation inhibitor. Moreover, rodents fed methionine-deficient diets exhibited both global hypomethylation and increased Dnmt-1 expression and activity (Slack et al 1999).…”
Section: Heterozygous Reeler Micementioning
confidence: 99%
“…Clearly excess dietary methionine is unlikely to be the cause; however, the finding of elevated CSF methionine in schizophrenics cited earlier (Regland et al 2004) may be relevant if confirmed in further studies. Conversely, animal studies demonstrate that methyl-deficient diets also increase Dnmt-1 activity (Christman et al 1993;Slack et al 1999). Rats fed a methyl-deficient diet for 1-4 weeks developed alterations in gene expression; RNA and Dnmt activity increased 2 -3-fold.…”
Section: Heterozygous Reeler Micementioning
confidence: 99%
“…Due to a preference for hemimethylated DNA, DNA methyltransferase 1 (DNMT1) is believed to be responsible for copying the DNA methylation pattern within the mother cell and maintaining the pattern of genomic methylation within the daughter cell (38). Several lines of evidence suggest a role for DNMT1 in cellular transformation (2,22,23,37,44): indeed, DNMT1 is upregulated in multiple human cancers (17, 33), and some colorectal cancers have been observed to bear mutations in DNMT1 (19). DNMT1 has therefore been proposed as a target for anticancer therapy (39).…”
mentioning
confidence: 99%
“…There is no evidence in the literature that decitabine, in addition to its binding to DNMT enzymes, can also act on the corresponding DNMT genes. Based on our results we can speculate two possibilities which involve a regulatory feedback mechanism in the DNA methylation machinery (18). Firstly, that decitabine directly acts on the DNMT promoters, which are known to have CpG-rich regions and hence are possibly methylated.…”
Section: Discussionmentioning
confidence: 67%
“…This is in contrast to other reports associating increased DNMT1 and DNMT3b expression with acquired drug resistance in murine neuroblastoma (16). Analysis of the DNMT3 promoter region revealed that the DNA methylation machinery itself is possibly regulated by DNA methylation (17,18). The 5' upstream region of the DNMT gene showed full promoter activity and this region lies within a CpG-rich site (17).…”
Section: Discussionmentioning
confidence: 99%